The Illusion of Meritocracy: State Hegemony and the Discourse of Exclusion in Indonesia’s Teacher Recruitment Policy - Pitriyani Pitriyani; Elly Malihah Setiadi; Tutin Aryanti (Jurnal Pendidikan Progresif, 2026)
The recruitment of government employees with work agreements (PPPK) is often seen as a space of hope for senior honorary officials who no longer meet the age requirements to participate in the civil servant candidate recruitment process. However, in reality, the policy is not supported by the regulatory apparatus, which sides with their position, thus placing senior honorary officers in a structural injustice. This study aims to critically examine the construction of meritocracy and state hegemony in the PPPK recruitment policy for senior honorary teachers in Lebak Regency, Banten, and to explore how they interpret their experiences and perceptions of the policy. This research used a qualitative-critical approach through the analysis of critical discourse, drawing on the thinking of Michel Foucault, or Foucauldian Discourse Analysis (FDA), developed by Kendall & Wickham. The power of meritocracy discourse works by ignoring the appreciation of age and work experience in the 2024 PPPK recruitment, prioritizing technocratic-procedural logic, normalizing uncertainty through overlapping and inconsistent regulations, and reproducing structural gaps due to limited formation and fiscal capacity. The repeated failures experienced by senior honorary teachers give rise to a sense of disrespect and exclusion by a system perceived as more favorable to young teachers. For them, the PPPK recruitment is not a fair meritocratic mechanism, but a process that ignores devotion while increasing the uncertainty of life. The PPPK recruitment policy operates through a meritocratic discourse that prioritizes objective standards. The state positions meritocracy as the fairest means of assessing the quality of PPPK-civil servants. The state maintains its hegemony by making senior honorary teachers accept the logic of meritocracy, even though it is detrimental to them, because it is presented as the only legal route to obtaining PPPK-civil servant status. Keywords: hegemony, honorary teachers, meritocracy, PPPK recruitment.